Analisis Faktor yang Mempengaruhi Minat Mahasiswa dalam Berinvestasi - Fatchan, Ilham Nuryana; Fatchan, Fuad Hudaya; Achyani, Fatchan; Wardana, Candra Kusuma; Kholillulloh, Fajar (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to examine the influence of capital market training, financial literacy, research benefits, and research motivation on the investment interest of students from the Faculty of Economics and Business at Muhammadiyah University of Surakarta. Data were collected using a questionnaire through purposive sampling, with 86 respondents. The research employed validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis. Findings from the t-test indicate that capital market training, financial literacy, investment benefits, and investment motivation significantly affect the investment interest of students in the Faculty of Economics and Business at Muhammadiyah University of Surakarta.